Biomex Quad Helix (Orthodontic Journal of Nepal, 2014)
Introduction: Anterior deep bite with narrow maxillary arch is a most common clinical situation orthodontists have to deal with in Class I as well as Class II malocclusions.Objective: To present a modification of the quad helix appliance which incorporates acrylic anterior bite plane for simultaneous bite opening with maxillary expansion (Biomex Quad helix). Appliance design: The appliance is made of 0.036 inch stainless steel wire. The anterior bridge of the quad helix is modified by extending it anteriorly. The wire is soldered to the stainless steel bands on the maxillary first permanent molars. Acrylic anterior bite plane is added to this anterior extension keeping the anterior helices exposed. It combines advantages of a quad helix with that of anterior bite plane. Hence it can be useful for simultaneous bite opening with maxillary expansion, deprogramming, and relieving TMJ symptoms by unlocking the occlusion.Conclusion: Biomex Quad Helix is a versatile appliance which is simple in design, easy to fabricate, comfortable for the patient, and economical for the operator and the patient.